House characteristics and condition as determinants of visible mold and musty odor: Results from three New Zealand House Condition Surveys in 2005, 2010, and 2015. (17th December 2020) - Taptiklis, Phoebe; Phipps, Robyn; Jones, Mark; Douwes, Jeroen
Abstract: This study assessed associations between house characteristics and mold and musty odor, using data from three consecutive (2005, 2010, and 2015) New Zealand House Condition Surveys, involving a total of 1616 timber‐framed houses. Mold, musty odor, and house characteristics were assessed by independent building inspectors. We used multivariate logistic regression analyses mutually adjusted for other house characteristics for each survey separately. Positive and independent associations were found with tenure, ventilation, insulation, and envelope condition for both mold in living and bedrooms and musty odor. In particular, we found significant dose‐response associations with envelope condition, ventilation, and insulation. Odds of mold increased 2.4–15.9 times (across surveys) in houses with the worst building envelope condition (BEC; p  < 0.05–0.001 for trend); optimal ventilation reduced the risk of mold by 60% and the risk of musty odor by 70%–90% ( p  < 0.01 for trend). Other factors associated with mold and musty odor included: tenure, with an approximate doubling of odds of mold across surveys; and insulation with consistent dose‐response patterns in all outcomes and surveys tested ( p  < 0.05 for trend in two surveys with mold and one survey for odor). In conclusion, this study showed the importance of BEC, ventilation, and insulation to avoiding harmful damp‐related exposures.